Defeitos induzidos por terras raras divalentes e trivalentes no Sr4Al14O25 - Bispo, Giordano Frederico da Cunha (2012)
In this work, the mechanisms of doping and the co-doping Sr4Al14O25 with divalent and trivalent rare earths ions, were studied using static computer modeling techniques. A set of potential parameters was developed that is able to reproduce the Sr4Al14O25 with a maximum lattice parameters difference of 2% and the involved metal oxides crystal structures with a maximum lattice parameters difference of 3%. Having achieved a reliable parameterization of the materials, defects could be modeled in the Sr4Al14O25 matrix. The possible mechanisms of the trivalent rare earth incorporation were studied and five mechanisms were proposed. For all of them, solution energies were calculated using two different approaches: the infinite dilution method, where only one defect is created in an infinite crystalline lattice, and the ideal solution method, that takes into account the defect concentration within the limits where no interaction between defects is considered. In the infinite dilution method, the solution energy values showed that the trivalent rare earths are divided in two groups: one group that goes from Lu3+ to Dy3+, at 0K, or from Lu3+ tol Gd3+, at 293K, which preferentially incorporated by isovalent substitution in one of the Al6 sites in octahedral coordination, and a second group that goes from Tb3+, at 0K, or Eu3+, at 293K, to Ce3+, which are dissolved in the matrix via aliovalent substitution in the Sr site, with a charge compensation mechanism given by O2- ions in interstitial positions. Pr3+ ions at 0K, is the only exception to this behaviour where Al vacancy or interstitial O2- can be the charge compensation defect. All solution energies for this method are positive values and show some reasonable difference between them. Ce3+ had the lowest solution global energy, showing this ion to be easily incorporated in the matrix. As for the ideal solution method, the solution energies can also be divided in two groups, as before but with no dependence on the temperature The Pr3+ ion is again an exception to this behavior. The ideal solution method has the advantage that all solution energies depend on the concentration of the dopants and this allows a rough evaluation of the solubility limit for each defect type. Using this method, the maximum rare earth doping concentration would be around 0.03%. Based on the results of the trivalent ions doping mechanism, some proposals to the trivalent reduction mechanism in the matrix were formulated. Each one of these mechanisms is governed by a solid state solution reaction and the solution energies were calculated using the associated energy balance equations. vi Several atmospheres were considered and both the infinite dilution and the ideal solution methods were used to calculate the solution energy. Both show the same behavior, except when the reducing environment is a mixed atmosphere, which is justified by the different quantities of gases used in each method. The results showed that the reduction is easier for the Eu3+ than for the other trivalent ion and that CO is the best atmosphere to promote this reduction, while the N2 atmosphere has a low reducing efficiency, which is in agreement to the results found in the literature. Concerning the environment close to the dopants, we concluded that the substitution of the Eu2+ at the Sr site does not modify the site significantly It was also studied the presence of a codoping ion in the matrix near Eu2+ doping ion. Three mechanisms were proposed and the solution energies were calculated. These results showed that the solution energy values have the same behavior showed by the trivalent ions, except by the co-dopant Eu3+ ion in the interstitial oxygen mechanism. The lowest energy values were obtained with a CO reducing atmosphere. Comparing the solution energies, it can be said that the mechanism in which the trivalent ion occupies the Al3+ site is more likely to happen with ions from Lu3+ until Sm3+, except at 0K, where the Sm3+ has more than one possibility. The Nd3+, Pr3+ and Ce3+ ions have preference for the compensation mechanism with interstitial oxygen. In all these cases the minimized structures around the isovalent substitution defects showed that the distance between the Eu2+, at the Sr site, and the M3+ ions, at the Al site, is rather small and that supports the direct charge exchange mechanim proposed by Nakazawa et. al. [1] to explain the phosphorescence mechanism in this matrix. On the other hand, for the cases where the aliovalent substitituion defect is formed with compensations by interstitial O2- ions, the distance between the Eu2+ and M3+ sites are large enough to avoid direct charge exchanges.